Analisis Perhitungan Biaya Pesanan dalam Menentukan Harga Pokok Produksi Job Order Costing Kue Karawo - Valentina Monoarfa; Juningsih Feronika; Indi Emilia Sari (ManBiz: Journal of Management and Business, 2024)
This study aims to analyze the calculation of order costs in determining the cost of production for Karawo Cakes using the job order costing method. This method allows the company to determine production costs more accurately by allocating direct and indirect costs to each specific order. In this research, data were collected through interviews and direct observation of the production process of Karawo Cakes at one of the SMEs in Gorontalo, namely Toko Karwo Li Maya. The results of the analysis indicate that the use of the job order costing method can provide more detailed and accurate information regarding the components of production costs, including raw materials, direct labor, and factory overhead. This information is crucial in determining competitive selling prices and improving production efficiency. Thus, the job order costing method helps the company improve the accuracy of production cost calculations and supports better decision-making in pricing strategies.